Social Economy and Third Sector - Gómez Álvarez, Juan Jesús (REVESCO. Revista de Estudios Cooperativos, 2022)
The work deals with the conceptualization and delimitation of two areas – the Social Economy and the Third Sector – analyzing the common contours and blurred borders at a time when both play a vital role due to the current economic and social arising from the measures adopted during the health crisis. To this end, the different types of entities of each sector are analyzed and their characteristics are further delved into, based on the extensive and rigorous work carried out by the doctrine and the multiple representative organizations, such as the Economic and Social Committee. These organizations have carried out the invaluable task of developing the concept of Social Economy which is capable of discerning between the private and public elements of the economy through the embodiment of what we know as the Charter of Principles of the Social Economy. Spain has been a pioneer in approving a Social Economy Law, although there is a lack of specific regulation with palpable legal application. On the other hand, the publication of the State Law of the Third Sector of Social Action represents a significant milestone. However, the absence of regulation on the generic figure leads to a degree of confusion regarding the entities integrated into the definition. This study aims to provide clarity on this aspect, focusing on the future of both sectors.